Faktor- Faktor Yang Berhubungan Dengan Keluhan Low Back Pain (LBP) Pada Nelayan Di Pelabuhan Perikanan Samudera Kota Kendari Tahun 2023 - Annisah Wulandari; Fifi Nirmala; Indah Ade Prianti (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Low Back Pain (LBP) is a health problem that causes restrictions on activities and also absence from work. Fishermen are people whose livelihood is fishing whose activities can place additional load on the muscles of the lower back and spine, which can cause stress and excess strain on the lower back region. According to the World Health Organization (WHO), musculoskeletal disorders in the world number 1,71 billion and low back pain is the 3rd health problem in the world.  The purpose of this study is to determine the factors associated with complaints of low back pain in fishermen at Pelabuhan Perikanan Samudera Kota Kendari in 2023. This study used a cross sectional study approach with a total sample of 85 people taken using accidental sampling techniques. The analysis carried out includes univariate analysis and bivariate usses the Chi-Square method. The results showed a relationship between age and LBP complaints (p-value = 0.020), and between period of work and LBP complaints (p-value = 0.049), but there was no relationship between length of work and LBP complaints (p-value = 0.417) and smoking habits and LBP complaints (p-value = 0.344).